The Survival Rate of Oreochromis niloticus Baby Fish During Closed Transportation at Different Road Condition - Ruddy Suwandi; Fajar Kurnia Budiman; Pipih Suptijah (Jurnal Pengolahan Hasil Perikanan Indonesia, 2007)
Fish transportation is an activity on moving fish from one place to another. Specific for live fish, the transportation process is so important due to the different value of live fish and the dead one, either in term of its price and or function. Live fish transportation, basically is a forcing fish in a new environment condition different with the usual one, along with sudden changes of ambient characteristic which threat the live of fish. The factors which influential on fish live transportation are fish condition and water quality. Beside these, other factor which also give influent is infrastructure of transportation (road, vehicle, etc.). The researched was done to know the effect of road surface quality (good, semi good, and bad) on survival rate (SR) of Oreochromis niloticus fish juvenile. The highest SR came from the good treatment is 88.33%, with the water quality are: DO (dissolve oxygen)=2.19 ppm; CO2=39.6 ppm;pH=6.02; alkalinity = 156.42 ppm; and temperature = 27.75oC. The lowest one came from the bad treatment is SR=0% with the water quality are: DO (dissolve oxygen)=1.71 ppm; CO2=53.46 ppm; pH=6.02; alkalinity=1,003.86 ppm; and temperature=27.5oC. The SR of juveniel fish transportation at a real condition from Bogor to Jakarta is 93.3%. The result indicated that types and time of treatment effected to the SR.Key words : infrastructure of transportation, fish transportation, survival rate